Rutin ameliorates obesity through brown fat activation. Issue 1 (20th October 2016) - Yuan, Xiaoxue; Wei, Gang; You, Yilin; Huang, Yuanyuan; Lee, Hyuek Jong; Dong, Meng; Lin, Jun; Hu, Tao; Zhang, Hanlin; Zhang, Chuanhai; Zhou, Huiqiao; Ye, Rongcai; et al.
Abstract : Increasing energy expenditure through activation of brown adipose tissue (BAT) is a critical approach to treating obesity and diabetes. In this study, rutin, a natural compound extracted frommulberry and a drug used as a capillary stabilizer clinically formany years without any side effects, regulated whole‐body energymetabolism by enhancing BAT activity. Rutin treatment significantly reduced adiposity, increased energy expenditure, and improved glucose homeostasis in both genetically obese (Db/Db) and diet‐induced obesity (DIO) mice. Rutin also induced brown‐like adipocyte (beige) formation in subcutaneous adipose tissue in both obesity mouse models. Mechanistically, we found that rutin directly bound to and stabilized SIRT1, leading to hypoacetylation of peroxisome proliferator‐activated receptor γ coactivator‐1α protein, which stimulated Tfam transactivation and eventually augmented the number of mitochondria and UCP1 activity in BAT. These findings reveal that rutin is a novel small molecule that activates BAT and may provide a novel therapeutic approach to the treatment of metabolic disorders.—Yuan, X., Wei, G., You, Y., Huang, Y., Lee, H. J., Dong, M., Lin, J., Hu, T., Zhang, H., Zhang, C., Zhou, H., Ye, R., Qi, X., Zhai, B., Huang, W., Liu, S., Xie, W., Liu, Q., Liu, X., Cui, C., Li, D., Zhan, J., Cheng, J., Yuan, Z., Jin, W. Rutin ameliorates obesity through brown fat activation. FASEB J. 31, 333–345 (2017) www.fasebj.org